KERAGAMAN JENIS MUSUH ALAMI PADA SERANGGA HAMA PADI SAWAH DI KABUPATEN MINAHASA SELATAN - Moningka, Mareyke; Tarore, Dantje; Krisen, Jeane (EUGENIA, 2012)
ABSTRACT The objective of this research was to know the diversity of natural enemies (parasitoid and predator) on wet rice-field, so that could be bread to control pest insects with a tactic that is easy, cheap, efficiently and environment safe. Catching a natural enemies species was conducted in district of Tumpaan and Tenga (which was the centre of rice production in South Minahasa Regency) by sweeping (using insects trap) and direct observation in the field. The specimen insect was brought to the laboratory for identified. Diversity was measured using Shannon-wavers, and then continued to decide the species abundance average level. The natural enemies species which were found consist of five ordos of predator (Araneida, Hemiptera, Odonata, Coleoptera, and Orthoptera); 10 families; and 16 species; two ordos, 10 families and 13 species of parasitoid. The result of variance analysis showed that the abundance average level (J) of 29 species (predators and parasitoid) which were found almost the same and this value refer to value that almost the same on the diversity in species group (H) during observation either the old crop stadia or the location of rice plant. Keywords: Diversity, natural enemies, insect pest